PENATAAN KORIDOR PERMUKIMAN KAMPUNG KARANG ANYAR BERBASIS PENGOLAHAN SAMPAH DAUR ULANG DI MAKASSAR - Arman, Nursahfika; Rahayu, Irma (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
Karang Anyar village located on the road Baji Dakka potential to become a pilot project for waste management in residential areas. Called pilot as inspiring, an example and shows the steps in processing waste-based nongovernmental for that organize corridor settlements Karang Anyar because they as a region used as a pilot project then certainly every corridor gave appeal to the community as well as processing activities in them should be contained with adequate facilities , as seen today in the village of Karang Anyar, where the activity of waste management is entrenched and everyone to participate in these activities, thus easier to now see is lacking spacial, see the design / Urban Design in this case whether it meets or accommodate all pengelolah activity or not. For example, not aesthetic enough people recycle garbage in each house, then there must be a hall where they gather, define targets, goals, step forward, a better method again in the processing of garbage, so that people can come together and jointly determine better methods to be made a pilot in waste processing. It is also the hall can be used as a space to hold an exhibition to display and demonstrate to outsiders who are invited to see the results of waste management and waste counseling measures. Moreover, it can be equipped school facilities for waste recycling education in which spaces are divided into five classes that are specific to managing a variety of trash found in the community.